Acute disseminated mycobacteriosis in captive Atlantic guitarfish (Rhinobatos lentiginosus). (November 2017) - Tuxbury, Kathryn A.; Young, Samuel A.; Bradway, Daniel S.; Marola, Jamie L.; Salfinger, Max; Garner, Michael M.
An adult female captive-born Atlantic guitarfish ( Rhinobatos lentiginosus ) was found acutely moribund on exhibit and died soon after presentation. Abnormalities on autopsy were focal cutaneous erythema on the tail, a small liver, many variably sized friable ovarian follicles, and coelomic effusion. Histologic examination revealed systemic bacterial embolization, and yolk coelomitis with minimal associated inflammation and some mineralization. Bacterial culture of blood and coelomic effusion grew a rapidly growing Mycobacterium species that was further identified as Mycobacterium chelonae by PCR amplification and sequencing of the RNA polymerase subunit beta ( rpoB ) gene of isolated genomic DNA. Concurrent reproductive disease may have caused immunosuppression, thus predisposing to the mycobacterial infection. At another institution, an adult male wild-caught Atlantic guitarfish was found dead on exhibit with no premonitory signs. Abnormalities on autopsy were a thin body condition, small liver, and coelomic effusion. Histologic examination revealed acute mycobacterial septicemia. M. chelonae was also identified in this fish by PCR amplification and sequencing. Mycobacteriosis has rarely been reported in captive elasmobranchs. Guitarfish may have greater susceptibility to mycobacteriosis than other elasmobranchs, and acute and chronic manifestations of the disease may exist in this species.